Kirk-Othmer Encyclopedia of Chemical Technology 2010
DOI: 10.1002/0471238961.phthsabn.a01
|View full text |Cite
|
Sign up to set email alerts
|

Phthalein Dyes

Abstract: Color change has fascinated individuals for a long time. Phthaleins dyes traditionally are used for color change, and they constitute the major class of pH indicators. This review presents systematic and up‐to‐date compiled data on commonly used phthalein dyes with references to the introduction, history, chemical structures, synthesis, color‐change mechanism, color and constitution, spectral data, applications, and health/safety factors. Phthalein dyes exhibit multiple applications, which are groupe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…It is possible to observe interesting results in the study carried out, because all the solutions showed significant changes in their coloration when they go from an acid medium to an alkaline medium . This effect is known as halochromism .…”
Section: Resultsmentioning
confidence: 99%
“…It is possible to observe interesting results in the study carried out, because all the solutions showed significant changes in their coloration when they go from an acid medium to an alkaline medium . This effect is known as halochromism .…”
Section: Resultsmentioning
confidence: 99%
“…The recalcitrant and xenobiotic natures of azo dyes can be shown to impact human and animal health in the form of severe pathologies. Indeed, azo dyes are considered carcinogenic and mutagenic organic chemicals [17][18][19][20][21][22][23][24][25][26][27]. Short-term exposure to azo dyes does not significantly impact human and animal health [18].…”
Section: The Health Impact Of Azo Dyesmentioning
confidence: 99%
“…The most widely used condensing agents are concentrated sulphuric acid and anhydrous zinc chloride. Table summarises a comprehensive list of various condensing agents reported in the literature for synthesising phthalein dyes along with the corresponding references . Recrystallisation to purify phthalein dyes on a large scale is also reported .…”
Section: Synthesismentioning
confidence: 99%
“…Although phthalein dyes have been extensively used in various fields, no review emphasising the developments in the chemistry of phthalein dyes has so far appeared. One book on acid–base indicators covers some of the phthalein dyes, and another reports on the most commonly used phthalein dyes , namely phenolphthalein, o‐ cresolphthalein and thymolphthalein.…”
Section: Introductionmentioning
confidence: 99%